Variations in soil moisture and their impact on land–air interactions during a 6-month drought period in Taiwan - Fang-Yi Cheng; Yi Chen (Geoscience Letters, 2018)
Abstract This work is a follow-up study to Lin and Cheng (J Hydrometeorol 17:1337–1355, 2016). In our previous study, the Weather Research and Forecasting model was applied to investigate the impact of soil moisture initialization and soil texture on land–air interactions for a short-term 1-month period, in which two typhoons hit Taiwan and the atmospheric condition were wet. In this study, we extend the simulation period to 6 months and target a drought period. The simulation period is from October 1, 2014 to March 31, 2015. During this study period, a lack of rain caused the drought and strict water rationing was enforced in Taiwan. The study objectives are (1) to understand the effect of soil moisture initialization and soil texture on land–air interactions during the 6-month drought period and (2) to identify the distinction between the previous study, where the atmospheric condition was wet, and the current 6-month drought period. Compared to the previous 1-month simulation, the land–air interactions are strengthened in the 6-month drought period, showing the enhanced impact of soil moisture variations on the surface heat flux, air temperature, and local circulation. In addition, the evapotranspiration process is strengthened in this study, indicating that the land–air interactions are significant when the atmospheric condition is dry. A soil moisture-limited evapotranspiration regime was identified in the previous 1-month wet period study, with the soil moisture strongly constraining the evapotranspiration. However, in this study, the evapotranspiration process can be independent of the soil moisture content, once the soil moisture is lower than the wilting point.